Forced Expiratory Volume in 1 Second and Forced Vital Capacity in Bronchial Asthma Patients in Relation with Asthma Exercise - Atika Andianti; Vita Murniati Tarawan; Hendarsyah Suryadinata (Althea Medical Journal, 2020)
Background: Aerobic physical activity is one of the non-pharmacology management approaches of asthma. The Asthma Foundation of Indonesia (Yayasan Asma Indonesia, YAI) has designed an aerobic physical activity for people with asthma, known as Asthma Exercise. Asthma exercise is expected to increase the overall functional capacity of the lungs. One way to measure lung function is by measuring the score of forced expiratory volume in 1 second (FEV1) and forced vital capacity (FVC). The objective of the study was to explore the difference in FEV1 and FVC between bronchial asthma patients with and without asthma exercise. Methods: This study involved asthma patients from the Bandung Asthma Association (Perhimpunan Asma Bandung, PAB) who did asthma exercise (n=28), and as control patients from the Pulmonology Clinic in Dr. Hasan Sadikin General Hospital were selected who did not do asthma exercise. The research data used were primary data from the spirogram examination. Asthma patients were selected based on inclusion and exclusion criteria. This research used unpaired numerical comparative analytical hypothetical tests with a cross-sectional design.Results: The study showed the mean of FEV1 and FVC in the group with asthma exercise (1.6107±0.3780L and 2.0396±0.3465L) was higher than the group without asthma exercise (1.3750±0.4702L and 1.7164±0.4632L). Statistical difference test using independent t-test indicated a score of p=0.044 for FEV1 and p=0.005 for FVC between the two groups.Conclusions: There are significant differences in FEV1 and FVC between bronchial asthma patients with and without asthma exercise. Furthermore, asthma exercise is recommended for asthma patients to improve their lung function.